PENGEMBANGAN "PAPRIKA" (PAPAN TARIK PANCASILA) SEBAGAI MEDIA UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS II SD MUHAMMADIYAH AMBARBINANGUN - Anisa Dita Cahyani; Ari Wibowo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop PAPRIKA (Papan Tarik Pancasila) as an instructional media to improve students learning achievement, ensuring that it is feasible, practical, and effective. Te research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The limited trial subjects consisted of 10 students from class II B at SD Muhammadiyah Ambarbinangun. The field trial was conducted at SD Muhammadiyah Ambarbinangun involving 28 students from class II A. Tests, questionnaires, and documentation were employed as data gathering methods. Both quantitative and descriptive analysis were used in data analysis methods. The validity and reliability of the tests instruments were examined using SPSS 26. The effect of PAPRIKA (Papan Tarik Pancasila) instructional media on students learning achievement was analyzed using normality tests and the Paired Sample t-Test. The results of the study showed that feasibility assessment from material experts reached 94% and from media experts 96,7% both categorized as “Highly Feasible”. The practically results based on teachers responses reached 95%, while students responses reached 91%. The effectiveness of the instructional media was determined through the Paired Sample t-Test, where the pretest and posttest results obtained a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest results. Therefore, PAPRIKA (Papan Tarik Pancasila) instructional media is feasible, practical, and effective in improving students learning achievements.